Pengembangan E-Modul Berbantuan Flipbook Berbasis Literasi Untuk Mata Kuliah Statistika - Kusumaningrum, Yulinda; Utomo, Victor Gayuh; Ellyawati, Hetty Catur; Maulana, Charis (Jurusan Teknologi Informasi Universitas Semarang, 2024)
Statistics is the basis for studying other subjects in the Informatics Engineering Study Program. However, some lecturers have not used teaching materials such as interactive modules to help students learn statistics. For this reason, research is needed which aims to (1) develop literacy-based Flipbook-assisted interactive e-modules in statistics courses that are valid, (2) determine the practicality of literacy-based Flipbook-assisted interactive e-modules in statistics courses for students. This type of research is Research and Development (R&D). The research subjects were 30 Informatics Engineering students taking Statistics courses. The development steps in this research are using ADDIE, namely Analysis, Design, Development, Implementation, and Evaluation. The research results obtained: 1) the literacy-based flipbook-assisted e-module that was developed was declared valid/feasible with an average percentage of material experts of 80% and media experts of 85.41%, 2) the flipbook-assisted interactive e-module that was developed met the criteria practically with a percentage reaching 75%.